Legal analysis of the implementation of the Immigration Management Information Sys-tem (SIMKIM) in passport services in Batam City towards transparent public service. - Jimmy Limou; Soerya Respationo; Ramon Nofrial (CV. RADJA PUBLIKA, 2025)
Ensuring everyone can see and understand how government services work is crucial. Thanks to new technology, the immigration office in Batam City has begun using a new computer system called SIMKIM to assist with passport services. This study examines how SIMKIM regulations were created, how it is used, and the challenges and solutions. The study discusses how the law supports SIMKIM, how workers and the public use it, and the challenges they face, such as a lack of computers or a lack of familiarity with digital devices. Overall, SIMKIM helps speed up, improve, and simplify the passport application process. The study suggests that to improve services, they need to improve regulations, provide more training to workers, build better computer systems, and teach more people how to use digital technology.